(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Does society, from the perspective of stakeholders, contribute to development in the organization and what does the organization need to consider in order to become an exceptional organization? Purpose: In the article, we present the importance of the inclusion of society, which contributes to the implementation and achievement of the organization’s goals. The goal of the research is to determine in what ways society as a key stakeholder contributes to the development of the organization and the achievement of organizational excellence. Method: We used a qualitative research method based on a systematic study of existing literature, articles, professional works and based on personal experience we gave an opinion and suggestions for possible improvements Results: One of the fundamental tasks of the organization, to achieve exceptionality in the sense of society, is to establish good relations with stakeholders, which leads to mutual benefit for both the organization and its society. The organization will involve key stakeholders in implementing and expanding its strategy and creating sustainable value, and will recognize their contribution in this area. Organization: An exceptional organization uses its purpose, vision and strategy to contribute to society. In doing so, it works in favor of mutual benefit - both for the organization and for its society. It is important that the organization fulfills society’s expectations. With all this, it guarantees its excellence. Society: It is important that the entire society, which is involved in the organization, is treated equally and that a high level of trust is maintained. There is also a strong emphasis on increasing diversity and inclusion and achieving a balanced gender representation. Originality: The originality of the article is that it focuses on one of the criteria of the EFQM 2020 model - society as a key stakeholder. Limitations/Future Research: We limited ourselves to similar research that has already been conducted in this area. Further research could deal with society, its aspects and expectations from a particular organization in even more detail.